Restoration of Skin Barrier Abnormalities with IL4/13 Inhibitors and Jak Inhibitors in Atopic Dermatitis: A Systematic Review - Chatzigeorgiou, Isidora; Koumaki, Dimitra; Vakirlis, Efstratios; Papadimitriou, Ilias; Gregoriou, Stamatios (Medicina (Kaunas, Lithuania), 2024)
Background and Objectives: Atopic dermatitis is a chronic inflammatory skin disorder with a significant burden on patients’ quality of life. This systematic review aims to evaluate the restoration of skin barrier abnormalities with interleukin-4/interleukin-13 (IL-4/IL-13) inhibitors and Janus kinase (JAK) inhibitors in atopic dermatitis. Materials and Methods: A comprehensive review of the literature was conducted, focusing on studies that assess the use of IL-4/IL-13 inhibitors and JAK inhibitors for atopic dermatitis. We identified eligible studies by searching Medline via PubMed with a special focus on their effect on the restoration of the epidermal barrier. Included studies evaluated the transepidermal water loss (TEWL), the reduction in epidermal thickness (ET), the improvement in ceramide synthesis, and the increase in stratum corneum hydration (SCH) with IL-4/IL-13 inhibitors and JAK inhibitors. The quality of included studies was assessed using the ROBINS-I and the RoB 2.0 tool for assessing the risk of bias. Results: Ten of the included studies concern dupilumab, while two concern JAK inhibitors. Ten were observational studies and two were randomized controlled trials (RCTs). The total number of included participants was 378 concerning dupilumab and 38 concerning JAK inhibitors. Five studies did not include any comparison group, three included healthy volunteers, two were conducted versus placebo, and two compared dupilumab with other treatments. The follow-up period ranged between 29 days and 32 weeks. The results demonstrated a significant decrease in transepidermal water loss (TEWL) and an increase in SCH on eczematous lesions for patients with sustained response to dupilumab treatment and observed improvements in ET and filaggrin (FLG) staining, which further support the efficacy of JAK inhibitors in enhancing skin barrier function. Conclusions: This review underscores the efficacy of IL-4/IL-13 inhibitors in improving skin barrier function. However, the limited number of studies focusing on JAK inhibitors and the overall lack of RCTs highlight the need for further research to establish the definitive role of IL-4/IL-13 inhibitors and JAK inhibitors in the restoration of the skin barrier.